Analysis of GNAT gene expression in Arabidopsis thaliana - Ranasinghe Arachchige, Umanga (My University, 2022)
In Arabidopsis thaliana (Arabidopsis), chloroplast localized GCN5 related N acetyltransferases (GNATs) are active acetyltransferase enzymes catalyzing two distinct acetylation reactions, i.e., N terminal and lysine acetylation of proteins. Eight GNAT proteins (GNAT1-7 and GNAT10) catalyze acetylation of various chloroplast proteins involved in photosynthesis. Moreover, GNAT1 and GNAT2 are involved in the biosynthesis of melatonin in plants. The aim of this study was to get an insight into the physiological functions of the GNAT enzymes through shedding light on the expression pattern of the GNAT genes in distinct plant organs. For the gene expression analysis, total RNA was extracted from Arabidopsis and RT qPCR analysis was performed. Further, isolated RNA was submitted to Turku Bioscience for the RNA-Seq, and data analysis is currently being performed. Thylakoid protein complexes from different organs were studied by using Blue Native gel electrophoresis. The results showed that the GNAT genes exhibited low expression levels in all plant tissues, especially in roots. Expression of GNAT1 and GNAT10 was upregulated in young rosettes indicating that the enzymes may be important for the metabolism of the developing leaves. GNAT7, in turn, showed high expression in both young and mature rosettes. In contrast to previous studies, our results did not show high expression of GNAT1 in flowers, possibly due to the differences in growth conditions. This study adds another piece to a puzzle aiming at increasing our understanding on the molecular mechanisms determining GNAT enzyme activity in Arabidopsis, and at linking GNAT gene expression, melatonin accumulation and various plastid properties in different plant organs.
Keywords: acetyltransferase, Arabidopsis thaliana, chloroplast, gene expression, GNAT